Low Contraceptive Use among Young Females in Uganda: Does Birth History and Age at Birth have an Influence? Analysis of 2011 Demographic and Health Survey - Kabagenyi, Allen; Habaasa, Gilbert; Rutaremwa, Gideon (Journal of contraceptive studies, 2016)
Globally adolescent fertility has been associated with increased risk to maternal and child health morbidity and mortality. The low use of contraception has been associated with high fertility levels, which is remains a public health concern that efforts have been raised to avert this. We examine the influence history of a previous birth and age at first birth would have on young women’s use of contraception. Methods—Using the 2011 Uganda Demographic and Health Survey data, we examine the predictors of contraceptive use on a sample of 3692 young females in Uganda. While controlling for education and age of respondents, logistic regression analyses were run to provide the net effect of the examined predictors on contraceptive use. The study variables included age of respondents, marital status, age at first birth, births in past five years, socioeconomic status, residence, region, education level, religion, occupation and whether the last child was wanted. Results—The findings show that only 12% of the adolescents were using contraception at the time of the survey. The key predictors of contraceptive use among young women in Uganda were age at first birth, history of previous birth, current age, and place of residence, education and socioeconomic status. Respondents who had a birth in the 5 years prior to the survey had five times (OR = 5.0, 95% CI = 3.7-6.5) the odds of contraceptive use compared to those who had never had a birth. Further, adolescent females with at least a secondary education were more likely to use contraceptives (OR = 1.55, 95% CI = 1.2-2.0) than those with primary education. The odds of contraceptive use were least among adolescents from Northern region (OR = 0.39, 95% CI = 0.2-0.6) compared to those from central region of Uganda. Muslim adolescent females were more likely to use contraceptives compared to Catholics (OR = 1.59, 95% CI = 1.1-2.3). Conclusion—There is great need to address issues that hinder young people from using contraception. Use of contraception and improving access to the services is highly recommended to avert some of the unplanned births among these females.
Keywords: Uganda; Adolescents; Contraception; Family planning; Females